ST6GALNAC1-mediated sialylation in uterine endometrial epithelium facilitates the epithelium-embryo attachment - Xinyue Dong; Hao Wang; Jinxuan Cai; Yichun Wang; Dezhi Chai; Zichen Sun; Jie Chen; Mengxia Li; Tianxia Xiao; Chunhua Shan; Jian V. Zhang; Ming Yu (Journal of Advanced Research)
Introduction: Embryo implantation requires synergistic interaction between the embryo and the receptive endometrium. Glycoproteins and glycan-binding proteins are involved in endometrium-embryo attachment. Sialyl Tn (sTn), a truncated O-glycan, is catalyzed by ST6 N-Acetylgalactosaminide Alpha-2,6-Sialyltransferase 1 (ST6GALNAC1) and can be detected by specific Sialic-acid-binding immunoglobulin-like lectins (Siglecs). Whether the sTn-Siglecs axis supports embryo implantation remains unknown. Objectives: This paper aims to study the role of ST6GALNAC1/sTn-Siglecs axis in embryo implantation. Methods: ST6GALNAC1 and sTn in human endometrium were analyzed by immunohistochemistry. An in vitro implantation model was conducted to evaluate the effects of ST6GALNAC1/sTn on the receptivity of human endometrial AN3CA cells to JAR spheroids. Immunoprecipitation combined with mass spectrometry analysis was carried out to identify the key proteins modified by sTn in endometrial cells. Siglec-6 in human embryos was analyzed by published single-cell RNA sequencing (scRNA-seq) datasets. Protein interaction assay was applied to verify the bond between the Siglec-6 with sTn-modified CD44. St6galnac1 siRNAs and anti-sTn antibodies were injected into the uterine horn of the mouse at the pre-implantation stage to evaluate the role of endometrial St6galnac1/sTn in embryo implantation. Siglec-G in murine embryos was analyzed by immunofluorescence staining. The function of Siglec-G is evidenced by uterine horn injection and protein interaction assay. Results: Both human and murine endometrium at the receptive stage exhibit higher ST6GALNAC1 and sTn levels compared to the non-receptive stage. Overexpression of ST6GALNAC1 significantly enhanced the receptivity of AN3CA cells to JAR spheroids. Inhibition of endometrial ST6GALNAC1/sTn substantially impaired embryo implantation in vivo. CD44 was identified as a carrier for sTn in the endometrial cells of both species. Siglec-6 and Siglec-G, expressed in the embryonic trophectoderm, were found to promote embryo attachment, which may be achieved through binding with sTn-modified CD44. Conclusion: ST6GALNAC1-regulated sTn in the endometrium aids in embryo attachment through interaction with trophoblastic Siglecs.